2006
DOI: 10.1063/1.2176857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perforated transparent electrodes on light transmittance and light scattering in substrates used for microcrystalline silicon thin-film solar cells

Abstract: The effect of a perforated transparent electrode, which is an electrode punctuated with holes, on light transmittance and light scattering was studied using textured ZnO:Ga formed by wet etching. The perforations were found to play a role not only in improving transmittance but also in maintaining high haze factor. The influence of the surface morphology of textured ZnO:Ga on the growth of hydrogenated microcrystalline silicon and on solar cell performance was also studied. It was found that, while the ZnO:Ga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…However, the large texture size can also decrease the electrical cell properties, because crystal growth on the steep texture gives rise to defective regions, like grain boundaries or voids, due to the collision of growth directions. [104][105][106][107] M. Python et al [107] analyzed a series of cells deposited on the LPCVD ZnO substrates treated with various plasma-treatment times, transforming the surface morphology from V shape (initial) to U shape (long treatment time). TEM observations indicated that the cells deposited on the U-shape substrate had less cracks than on the V-shape substrate, as shown in Fig.…”
Section: Relation Between Textured Zno and Solar Cell Performancesmentioning
confidence: 99%
“…However, the large texture size can also decrease the electrical cell properties, because crystal growth on the steep texture gives rise to defective regions, like grain boundaries or voids, due to the collision of growth directions. [104][105][106][107] M. Python et al [107] analyzed a series of cells deposited on the LPCVD ZnO substrates treated with various plasma-treatment times, transforming the surface morphology from V shape (initial) to U shape (long treatment time). TEM observations indicated that the cells deposited on the U-shape substrate had less cracks than on the V-shape substrate, as shown in Fig.…”
Section: Relation Between Textured Zno and Solar Cell Performancesmentioning
confidence: 99%
“…Over the past few years, tremendous efforts have been made to boost the power conversion efficiency (PCE) of a dye sensitized solar cell (DSSC) due to its technical feasibility and costeffectiveness alternative to silicon or III-V material-based solar cells. [15][16][17][18][19] Recently, for this, biomimetic architectures consisting of nano, micro, or compound (e.g., hierarchical nano/micro configuration) structures have been widely studied in several solar cells. 12 Additionally, an undyed layer placed on the top of the active layer 13 or a mirrorlike Pt counter electrode 14 was also studied as an internal rear reflector.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] For conformable and elastomeric stamps, in most of reports on the so lithography, polydimethylsiloxane (PDMS) with low free surface energy, exibility, transparency, and hardness has been oen used to transfer micro/nano patterns precisely on secondary substrates. [33][34][35] Meanwhile, the superhydrophilicity makes water droplets to spread out evenly like a thin lm on the surface. [25][26][27][28] These polymers are suitable for ARCs on the surface of the Si due to relatively low refractive indices of $1.4-1.7.…”
Section: Introductionmentioning
confidence: 99%